Portuguese trade with european union : an analysis of trade types and quality ranges - Fontoura, Maria Paula (2022)
In this paper several indexes based on unit prices were used to characterise the trade types and quality ranges of Portuguese trade with the European Union. The results allow us to question some of the traditional conclusions regarding the meaning of an increase of lIT. In general we concluded that ITT (and its increase) was mainly due to vertical differentiation and Portugal is, on average, more specialised in products of a lower quality. Thus, it is possible that trade patterns are changing without a significant alteration of the traditional trade determinants, at least in some sectors. Besides, the analysis undertaken allows insights on the consequences of an increase of competition when productive structures of different countries are compared on the basis of their quality ranges. For the sectors selected, we concluded that clothing and footwear apparently show a stronger specialisation in Portugal in products of a relatively higher quality, but the same cannot be said for textiles.